Host associated strains within Ugandan populations of the whitefly Bemisia tabaci (Genn.), (Hom., Aleyrodidae) - Legg, James P. (Wiley, 1996)
Studies were undertaken to investigate host relationships of populations of Bemisiu tubuci taken from the major crop hosts in Uganda. B. tubuci adults taken from cotton and sweet potato did not colonize cassava. None survived for longer than two days and nymphs emerging from eggs laid on cassava died. Cassava B. tubaci in contrast showed limited colonization on cotton and sweet potato and adults emerging from cotton retained the ability to colonize cassava, confirming the genetic basis of the distinction between 'strains' suggested by previous isozyme studies. The implications of these findings with regard to the role of B. tubuci in the epidemiology of African cassava mosaic geminivirus are discussed.